دراسة تصنيفية للعوالق الحيوانية- الدوّارات- في أحواض وحدة السن لتربية الأسماك – بانياس - بطل, محمد; زيني, أديب; جابر, خلدون (Latakia University Journal -Biological Sciences Series, 2017)
تعدّ معظم الدوارات Rotiferaجزء مهم من العوالق الحيوانية في النظام البيئي للبحيرات وأحواض تربية أسماك المياه العذبة، وتشكل مع متفرعات القرون Cladoceraومجذافيات الأرجل Copepoda معظم عوالق المياه العذبة التي تشكّل بدورها المستوى الغذائي الثاني والثالث في السلاسل الغذائية للأسماك واللافقاريات الأخرى.أجريت لأول مرة دراسة تصنيفية للدوارات في خمسة مواقع ضمن أحواض وحدة السن لتربية الأسماك في عرب الملك – بانياس كمساهمة في دراسة التنوع الحيوي المائي في المياه العذبة السورية وذلك خلال الفترة الزمنية الواقعة من بداية شهر تشرين الثاني 2013م وحتى أذار 2015م وبمعدل اعتيان واحد شهرياً. تم تسجيل 15 نوعاً جديداً من الدوارات لأول مرة في سوريه،تنتمي إلى اثنتا عشر جنسا ًمنتمية بدورها إلى تسعة فصائل. لوحظ تنوع وغزارة في أنواع فصيلة Brachionidaeحيث سجل منها 5أنواع جديدة.The Rotifera is considered one of the most important Zooplankton in the fish farming Ecosystems of Fresh water lakes and fish farming ponds .And it forms with Cladocera, and Copepoda, most of the fresh water Zooplankton which in turn occupies the second and third levels through the food Chains of the fish and other invertebrates .Taxonomical study of Rotifera in five stations in AL- Sinn's fish ponds is found out for first time and considered a contribution to study the Syrian fresh water Biodiversity during period from November 2013 to March 2015,by one sampling a month.Fifteen species to Syrian,s fauna were recorded for the first time of rotiferas belonged to twelve genera which by turn are related to nine families reported.Abundance and diversity were noticed in Brachionidae family which included five new species.